Adhesive composition

JP7635800B2Active Publication Date: 2025-02-26RESONAC CORP
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2023106956
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-02-26
Estimated Expiration
2039-04-11

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、クロロプレン重合体ラテックスが、特定サイズの無機フィラーを含むことで、著しく結晶化速度が増大し、初期接着強度が向上する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635800000003
    Figure 0007635800000003
  • Figure 0007635800000004
    Figure 0007635800000004
  • Figure 0007635800000001
    Figure 0007635800000001
Patent Text Reader

Abstract

To provide a sticking and adhesive composition that allows an increased crystallization rate of a sticking and adhesive agent, and allows improvement in initial adhesive strength.SOLUTION: The present invention relates to a sticking and adhesive composition that contains a chloroprene polymer latex, and an inorganic filler with a number average particle size of 10-150 nm measured by dynamic light scattering, and a sticking and adhesive layer obtained by drying the sticking and adhesive composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chloroprene polymer latex containing an inorganic filler, and mainly to a composition that enables an improvement in the crystallization rate of a chloroprene polymer. [Background technology]

[0002] Chloroprene polymer latex is widely used as a water-based pressure-sensitive adhesive for porous materials such as polyurethane foam.

[0003] In these applications, the film strength and adhesive strength are developed as the chloroprene polymer crystallizes, so a fast crystallization rate of the chloroprene polymer is very important for the function as an adhesive.

[0004] Patent Document 1 below discloses a chloroprene polymer latex containing 2-chloro-1,3-butadiene as a main monomer component, characterized in that the gel content in the solid content of the polymer latex is less than 3 mass %, the weight average molecular weight of a tetrahydrofuran soluble component in the solid content of the polymer latex is 550,000 to 1,100,000 and the molecular weight distribution (Mw / Mn) is in the range of 2.0 to 3.1, and the crystallization rate R expressed by the hardness increase at -10°C of the dried solid content of the polymer latex (R is the time required for the hardness to increase by 30 points from the initial (time = 0) hardness measured at -10°C according to JIS-K6301) is less than 60 minutes.

[0005] The following Patent Document 2 discloses an adhesive containing an aqueous polymer dispersion containing the following components (a) and (b): (a) a dispersion of polychloroprene having an average particle size of 60 to 220 nm, and (b) An aqueous silicon dioxide dispersion is disclosed in which the SiO2 particles having hydroxyl groups on the particle surface have a particle size of 1 to 400 nm. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] WO 08 / 026671 [Patent Document 2] Patent No. 5405258 [Non-patent literature]

[0007] [Non-Patent Document 1] Amemiya and Shinohara, "Fundamentals and Future Developments of Small-Angle X-ray Scattering", Synchrotron Radiation, Japan Synchrotron Radiation Research Society, November 2006, Vol. 19, No. 6, pp. 338-348 Summary of the Invention [Problem to be solved by the invention]

[0008] Patent Document 1 aims to provide an aqueous adhesive composition that provides high initial strength (wet strength), particularly in a wet state, after being applied to and bonded to an adherend support, and obtains a desired initial peel adhesion strength by controlling the polymerization temperature and the concentration of added chain transfer agent, but does not mention or suggest the addition of a nucleating agent during drying.

[0009] Patent Document 2 describes an object of providing a chloroprene polymer latex for adhesives having excellent adhesive strength (contact property) and an excellent balance between initial adhesive strength and water resistance, and refers to the silica particle size, but does not describe or suggest the technical idea of ​​setting a specific range within which the silica particles do not undergo secondary aggregation.

[0010] In conventional technology, in order to increase the crystallization rate of chloroprene polymer and improve the initial adhesive strength, it is necessary to polymerize the chloroprene polymer at a lower temperature. However, when polymerization is performed at a low temperature, it is necessary to cool the reaction tank with a larger refrigerator, and there is also a lower limit to the polymerization temperature due to the freezing temperature (0°C) of water, which is the dispersion medium in emulsion polymerization, so there is a limit to the improvement of the initial adhesive strength.

[0011] The present invention has been made under such circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive composition which can increase the crystallization rate and improve the initial adhesive strength. [Means for solving the problem]

[0012] Under such circumstances, the present inventors conducted extensive research and found that the inclusion of an inorganic filler as a nucleating agent in a chloroprene polymer latex significantly increases the crystallization rate of the chloroprene polymer latex and improves the initial adhesive strength, thereby completing the present invention.

[0013] That is, the present invention is configured as follows. [1] A pressure-sensitive adhesive composition comprising a chloroprene polymer latex and an inorganic filler having a number average particle diameter of 10 to 150 nm as measured by dynamic light scattering. [2] The adhesive composition according to [1], wherein the inorganic filler is silica. [3] The adhesive composition according to [2], wherein the silica is colloidal silica particles. [4] The adhesive composition according to any one of [1] to [3], wherein a volume ratio (based on the solid content) of the chloroprene polymer latex to the inorganic filler is 2 to 40. [5] A pressure-sensitive adhesive layer obtained by drying the pressure-sensitive adhesive composition according to any one of [1] to [4]. [6] The pressure-sensitive adhesive layer according to [5], which contains a non-agglomerated inorganic filler. Effect of the Invention

[0014] According to the present invention, the chloroprene polymer latex contains an inorganic filler having a specific size, so that the crystallization rate is significantly increased and the initial adhesive strength is improved. [Brief description of the drawings]

[0015] [Figure 1] The results of crystallization time measurement by differential scanning calorimetry are shown. [Diagram 2] The results of small angle X-ray scattering measurements are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below, but the present invention is not limited to the following embodiments. The adhesive composition [C] of the present invention contains at least a chloroprene polymer latex [A] and an inorganic filler [B]. In one embodiment of the present invention, the adhesive composition [C] is at least dried to form an adhesive layer [D]. Drying, also called casting, is a method of obtaining a film by dispersing or dissolving in a solvent and volatilizing it.

[0017] Chloroprene polymer latex [A] The chloroprene polymer used in the present invention is based on a polymer containing 100% by mass of 2-chloro-1,3-butadiene (chloroprene), but other copolymerizable monomers, such as 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, acrylic acid and its esters, methacrylic acid and its esters, etc., can be used within a range that does not impair the object of the present invention. Two or more types may be used as necessary. The content of other copolymerizable monomers in the total of chloroprene monomer and copolymerizable monomer is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 0% by mass, of the total of chloroprene and copolymerizable monomer. If the content of other copolymerizable monomers is 5% by mass or less of the total of chloroprene monomer and copolymerizable monomer, a good crystallization rate, i.e., initial adhesive strength, can be obtained, which is preferable.

[0018] The chloroprene polymer latex can be produced by aqueous emulsion polymerization, in which the dispersion medium is water. As the emulsifier in the aqueous emulsion polymerization method, an anionic emulsifier is preferred. In particular, it is preferred to use potassium salt or sodium salt of rosin acid or a combination of these, in that it is easy to stabilize the colloidal state and destabilize for forming an adhesive layer by adjusting the pH. Potassium salt or sodium salt of rosin acid or a combination of these is stable when the pH of the chloroprene polymer latex is in the range of 10.0 to 13.5. If the pH is 10.0 or more, good stability is maintained, so the chloroprene polymer does not aggregate, resulting in a good crystallization rate, i.e., good initial adhesive strength, and is preferred. If the pH is 13.5 or less, the ionic strength is small, and aggregation between colloidal particles is unlikely to occur, which is preferred.

[0019] The amount of emulsifier used is preferably 0.5 to 8.0 parts by mass, more preferably 1.0 to 5.0 parts by mass, and most preferably 1.5 to 4.0 parts by mass, based on 100 parts by mass of the total of the chloroprene monomer and the copolymerizable monomer. If the amount of emulsifier is 0.5 parts by mass or more, the chloroprene polymer particle size is small, so that the film-forming property when pressed when used as an adhesive is good, which is preferable. If the amount of emulsifier is 8.0 parts by mass or less, the amount of emulsifier in the chloroprene polymer latex is not excessive, so that a good crystallization speed can be obtained, foaming during drying can be suppressed, and the color tone of the product can be suppressed, which is preferable.

[0020] Furthermore, an emulsifying aid can be used to prevent aggregation between chloroprene polymer particles. As the emulsifying aid, an anionic emulsifying aid such as dodecylbenzenesulfonate salts such as sodium dodecylbenzenesulfonate and triethanolamine dodecylbenzenesulfonate, diphenylethersulfonate salts such as sodium diphenylethersulfonate and ammonium diphenylethersulfonate, and naphthalenesulfonate salts such as sodium salt of β-naphthalenesulfonic acid formaldehyde condensate can be used in combination. In addition, as a nonionic emulsifying aid, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene lauryl ether, etc. can be used in combination.

[0021] The amount of these emulsifiers used is preferably 0.05 to 1.00 parts by mass, more preferably 0.10 to 0.50 parts by mass, and even more preferably 0.20 to 0.30 parts by mass, based on 100 parts by mass of the total of the chloroprene monomer and the copolymerizable monomer. When the amount is 0.05 parts by mass or more, good dispersion is obtained, the formation of aggregates is suppressed, and good adhesive appearance is obtained, which is preferable. When the amount is 1.00 parts by mass or less, the emulsifier is unlikely to remain, so that the water resistance of the polymer is good, resulting in good adhesive strength and bonding strength, and also, foaming during drying is suppressed and good color tone of the product is obtained, which is preferable.

[0022] In order to adjust the molecular weight or molecular weight distribution, a chain transfer agent can be used. The chain transfer agent is not particularly limited, but preferably, dialkyl xanthogen disulfide, alkyl mercaptan, etc. can be used, more preferably, alkyl mercaptan, and further preferably, n-dodecyl mercaptan.

[0023] Examples of dialkyl xanthogen disulfides include diisopropyl xanthogen disulfide, diethyl xanthogen disulfide, dicyclohexyl xanthogen disulfide, dilauryl xanthogen disulfide, and dibenzyl xanthogen disulfide. Examples of alkyl mercaptans include n-dodecyl mercaptan, n-decyl mercaptan, and octyl mercaptan. Two or more types of chain transfer agents can be used in combination as long as the object of the present invention is not hindered. The amount of the chain transfer agent to be added varies depending on the type and the desired polymerization conversion rate. For example, when n-dodecyl mercaptan is used, it is preferably added in an amount of 0.05 to 0.20 parts by mass, more preferably 0.07 to 0.15 parts by mass, and even more preferably 0.09 to 0.11 parts by mass, based on 100 parts by mass of chloroprene and copolymerizable monomers in total.

[0024] The polymerization conversion rate of the monomer in the polymer is preferably 65 to 90%, more preferably 70 to 85%, and even more preferably 73 to 80%. When the polymerization conversion rate is 65% or more, the desired solid content of the polymer latex is obtained, the drying process after the adhesive application is facilitated, uniform adhesive strength is obtained, and a good polymer with less odor is obtained because of the small amount of residual monomer. When the polymerization conversion rate is 90% or less, the polymer has few branches and an appropriate molecular weight distribution, which is preferable. From this viewpoint, in the present invention, the adjustment of the polymerization conversion rate is extremely important. The polymerization conversion rate is controlled by adding a polymerization terminator described later at the time when the target conversion rate is reached to stop the reaction.

[0025] The polymerization temperature is preferably 0 to 30° C., more preferably 3 to 20° C., and further preferably 5 to 15° C. A polymerization temperature of 0° C. or higher is preferable because good productivity, contact properties, and water resistance of the polymer can be obtained. A polymerization temperature of 30° C. or lower is also preferable because the crystallization rate becomes sufficiently fast.

[0026] The gel content in the solid content of the chloroprene polymer latex [A], i.e., the amount of tetrahydrofuran (THF) insoluble matter, is preferably 3% by mass or less, more preferably 2% by mass or less, and further preferably 1% by mass or less. When the gel content in the solid content of the chloroprene polymer latex is less than 3% by mass, good water resistance is obtained, which is preferable. The content of tetrahydrofuran insoluble matter in the chloroprene polymer latex can be measured, for example, as follows. 0.5 g of chloroprene polymer latex containing water in the range of 40% by mass to 65% by mass is dropped into 100 mL of tetrahydrofuran, shaken overnight, and then separated by a centrifuge to obtain a supernatant dissolved phase. The obtained dissolved phase is heated to 100° C., and the tetrahydrofuran is evaporated and dried over one hour, and the mass of the dissolved matter dissolved in the dissolved phase is measured. The mass of the dissolved matter is subtracted from the mass of the chloroprene polymer in the chloroprene polymer latex to calculate the tetrahydrofuran insoluble matter. Here, the mass of the chloroprene polymer can be approximated by the mass of the solid content of the chloroprene polymer latex.

[0027] As the polymerization initiator, a conventional radical polymerization initiator can be used. For example, organic or inorganic peroxides such as benzoyl peroxide, potassium persulfate, ammonium persulfate, etc., and azo compounds such as azobisisobutyronitrile, etc. can be used. In addition, a cocatalyst such as anthraquinone sulfonate, potassium sulfite, sodium sulfite, etc. can be used as appropriate.

[0028] In general, in the production of chloroprene polymers, a polymerization terminator is added to terminate the reaction when a predetermined polymerization conversion rate is reached in order to obtain a polymer with a desired molecular weight and distribution. There are no particular limitations on the polymerization terminator, and commonly used polymerization terminators such as phenothiazine, para-t-butylcatechol, hydroquinone, hydroquinone monomethyl ether, and diethylhydroxylamine can be used.

[0029] Since chloroprene polymers are generally susceptible to deterioration by oxygen, it is desirable to use a stabilizer such as an acid acceptor or an antioxidant appropriately within a range that does not impair the effects of the invention.

[0030] It is preferable to further add 0.01 to 5.00 parts by mass of an acid acceptor and 0.1 to 3.0 parts by mass of an antioxidant to 100 parts by mass of the solid content of the chloroprene polymer latex. When the acid acceptor or antioxidant is insoluble in water or when it destabilizes the colloidal state of the polymer latex, an aqueous dispersion is prepared in advance and then added to the polymer latex. When the acid acceptor or antioxidant is within the above concentration range, it is preferable to obtain a composition having improved stability over time in adhesive strength and heat resistance.

[0031] The acid acceptor is not particularly limited, but specific examples include zinc oxide and hydrotalcite (manufactured by Kyowa Chemical Industry Co., Ltd.; DHT-4A (registered trademark), DHT-6). Two or more of these can be used in combination. The amount of these acid acceptors added is preferably 0.01 to 5.00 parts by mass, more preferably 0.05 to 1.00 parts by mass, based on 100 parts by mass of the solid content of the chloroprene polymer latex. When the amount is 0.01 part by mass or more, neutralization of hydrochloric acid released from the polymer over time is sufficient, which is preferable. When the amount is 5.00 parts by mass or less, good adhesion and bonding strength can be obtained, which is preferable.

[0032] In adhesive applications, from the viewpoint of preventing discoloration of glueline and sanitation, phenol-based antioxidants, particularly hindered phenol-based antioxidants, are preferably used as the antioxidant. Examples of such hindered phenol-based antioxidants include 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), and butylated reaction products of p-cresol and dicyclopentadiene. The amount of antioxidant added is preferably 0.1 to 3.0 parts by mass, more preferably 0.5 to 2.0 parts by mass, based on 100 parts by mass of solid content of the chloroprene polymer latex. When the amount of antioxidant added is 0.1 parts by mass or more, sufficient antioxidant effect can be obtained, which is preferable. If the amount of antioxidant added is 3.0 parts by mass or less, good adhesion and bonding strength can be obtained, which is preferable.

[0033] If necessary, additives other than the acid acceptor and antioxidant may be used as long as they do not impair the effects of the present invention. That is, tackifiers, pigments, colorants, wetting agents, defoamers, thickeners, etc. may be appropriately used.

[0034] Inorganic filler [B] Examples of the inorganic filler of the present invention include silica (white carbon, diatomaceous earth, calcined diatomaceous earth, quartz, cristobalite, colloidal silica, etc.), silicates (kaolinite, kaolin clay, calcined clay, talc, etc.), calcium carbonate, barium sulfate, titanium oxide, basic magnesium carbonate, dolomite, aluminum oxide, etc. Of these, the inorganic filler is preferably silica, and more preferably colloidal silica.

[0035] The particle size of the inorganic filler is 10 to 150 nm, preferably 40 to 140 nm, more preferably 100 to 130 nm, as measured by dynamic light scattering. If the number average particle size measured by dynamic light scattering is 10 nm or more, the inorganic filler particles do not aggregate with each other, and the chloroprene polymer latex particles are well dispersed as a nucleating agent, which is preferable. If the number average particle size measured by dynamic light scattering is 150 nm or less, the inorganic filler acts well as a nucleating agent, and the crystallization speed can be improved, which is preferable.

[0036] Adhesive composition [C] The pressure-sensitive adhesive composition [C] of the present invention contains at least a chloroprene polymer latex [A] and an inorganic filler [B].

[0037] The volume ratio of the solid content of the chloroprene polymer latex [A] to the solid content of the inorganic filler [B] is preferably 2 to 40, more preferably 3 to 30, and even more preferably 4 to 20. If the volume ratio of the solid content of the chloroprene polymer latex [A] to the inorganic filler [B] is 2 or more, the inorganic filler acts as a nucleating agent and increases the crystallization rate, which is preferable. If the volume ratio of the solid content of the chloroprene polymer latex [A] to the inorganic filler [B] is 40 or less, the concentration of the chloroprene polymer latex is appropriate, and an appropriate crystallization rate is obtained, which is preferable. The crystallization rate can be used as an alternative index of the initial adhesive strength.

[0038] The volumes of the solid content of the chloroprene polymer latex [A] and the solid content of the inorganic filler [B] are calculated by dividing the solid content concentrations of the chloroprene polymer latex [A] and the inorganic filler [B] by their respective densities.

[0039] Adhesive layer [D] The adhesive layer [D] of the present invention is produced by drying at least the adhesive composition [C]. In this specification, drying is also called casting, and is a method of obtaining a film by dispersing or dissolving in a solvent and volatilizing it.

[0040] The preferred range in which the particles do not undergo secondary aggregation can be determined from the ratio of the result of measuring the particle size of the inorganic filler in the adhesive layer [D] by small angle X-ray scattering (hereinafter sometimes referred to as SAXS) to the result of measuring the number average particle size of the inorganic filler by dynamic light scattering (hereinafter sometimes referred to as DLS). In order to confirm that secondary aggregation occurs in the adhesive layer [D], the ratio of the result of measuring the particle size of the inorganic filler in the adhesive layer [D] by SAXS to the result of measuring the number average particle size of the inorganic filler by dynamic light scattering is preferably 5 or more, more preferably 4 or more, and even more preferably 2 or more.

[0041] The crystallization rate of the adhesive layer [D] is calculated by taking the reciprocal of the time when the amount of heat absorbed per unit time in the differential scanning calorimetry (hereinafter sometimes referred to as DSC) of the adhesive layer [D] shows a maximum value (peak). -1 The specific method for measuring the crystallization rate is shown in the Examples. The crystallization rate was 0.065 min -1 More preferably, 0.066 min or more. -1 More preferably, 0.067 min -1 That's all.

[0042] Suitable adherends for the pressure-sensitive adhesive layer [D] in the present invention include, for example, foams made of materials such as polyurethane, ethylene-vinyl acetate copolymer, and polyethylene, as well as adherends such as wood, cloth, and textiles.

[0043] [Particle size measurement of inorganic fillers using small angle X-ray scattering] The average particle size of the inorganic filler in the chloroprene polymer according to one embodiment of this embodiment can be obtained as follows.

[0044] The particle size 2R of the inorganic filler was calculated by fitting the measurement data to the following formula (1) described in Non-Patent Document 1.

number

[0045] The present invention will be described below with reference to examples, but the present invention is not to be construed as being limited thereto.

[0046] <Differential scanning calorimetry> 2 ml of the adhesive composition [C] is measured out onto an aluminum dish (diameter 4 cm), heated to 105°C in an oven (DKN402, manufactured by Yamato Scientific Co., Ltd.), and dried for 30 minutes while maintaining the temperature at 105°C to prepare an adhesive layer [D]. Differential scanning calorimetry (hereinafter sometimes referred to as DSC) was carried out using a DSC7200 manufactured by Seiko Instruments Inc. 5 mg of the pressure-sensitive adhesive layer [D] obtained above was used as a sample. After holding at 60°C, which is above the melting point of the chloroprene polymer, for 5 minutes, the temperature was lowered at 10°C per minute to 2°C, and from the time when it reached 2°C, it was held at 2°C for 60 minutes, during which the heat generation due to crystallization was measured. The time was measured from the time when it reached 60°C, and the reciprocal of the time when the amount of heat absorption per hour showed a maximum value (peak) was regarded as the crystallization rate of the adhesive / adhesive.

[0047] <Particle size by dynamic light scattering method> The particle size of the inorganic filler was measured using a Zetasizer Nano S manufactured by Malvern Panalytical, and the volume average particle size was measured by dynamic light scattering (hereinafter sometimes referred to as DLS), and converted to obtain the number average particle size.

[0048] <Polymerization Conversion Rate and Solids Concentration of Chloroprene Polymer Latex> The solid content and polymerization conversion rate of the chloroprene polymer latex were calculated by the following formulas. Solid content concentration (mass%) = [(mass after drying at 141°C for 30 minutes) / (mass of latex before drying)] x 100 Polymerization conversion rate [%] = [(amount of polymer produced / amount of chloroprene monomer charged)] x 100 Here, the amount of polymer produced is calculated by subtracting the solid content other than the polymer from the solid content after polymerization. The solid content other than the polymer was calculated from the amount of the components that did not volatilize at 141°C from the amount of the polymerization raw materials charged.

[0049] <Particle size of inorganic filler measured by small angle X-ray scattering> Using a 0.5 mm thick adhesive layer [D] as a sample, small angle X-ray scattering measurements (using the second hatch at SPring-8 BL03XU) were performed to measure the particle size of the inorganic filler. The measurement conditions were: camera length (distance between sample and detector) 2.26 m, X-ray wavelength 0.1 nm, detector PILATUS, measurement range of scattering vector q 0.04 nm -1 ~0.8nm -1 It was decided. When fitting the particle size of 9 nm, the following was substituted into equation (1): Δρ: 1 (Any value can be entered as it does not affect the horizontal axis) V: 1 (Any value can be entered as it does not affect the horizontal axis) θ:2.4×10 -3 ~3.75 λ:0.1 R: 4.5

[0050] [Synthesis Example 1] Using a reactor with an internal volume of 60 liters, 20 kg of chloroprene monomer (manufactured by Showa Denko K.K.), 20 g of n-dodecyl mercaptan (chain transfer agent, manufactured by Tokyo Kasei Kogyo Co., Ltd.), 300 g of potassium rosinate (manufactured by Arakawa Chemical Industries Co., Ltd., R-300), 50 g of sodium dodecylbenzenesulfonate (manufactured by Kao Corporation, Neopelex (registered trademark) G-15), 19 kg of ion-exchanged water, 200 g of potassium hydroxide (special grade product manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.), and 20 g of potassium sulfite were charged and emulsified, and polymerization was carried out at 20°C under a nitrogen gas atmosphere using potassium persulfate as an initiator. When the polymerization conversion rate reached 79%, an emulsion of phenothiazine was immediately added to stop the polymerization, and steam was added to perform stripping, to obtain a chloroprene polymer latex (solid concentration 44%).

[0051] [Example 1] To 20 g of the chloroprene polymer latex synthesized in Synthesis Example 1, 3.8 g of colloidal silica (Snowtex (registered trademark) ZL) (15 parts by volume of silica particle solid content per 100 parts by volume of the chloroprene polymer latex solid content) was added, and the mixture was stirred at 23°C for 5 minutes to obtain a pressure-sensitive adhesive composition. Note that when calculating the volume, the density of chloroprene was 1.23 g / cm. 3 , the density of colloidal silica is 2.20g / cm 3 was used.

[0052] [Examples 2 and 3, Comparative Examples 1 to 3] The same procedure as in Example 1 was carried out except that the amount of inorganic filler added was as shown in Table 1.

[0053] The reagents used are as follows: Snowtex (registered trademark) ZL: Silica particles manufactured by Nissan Chemical Co., Ltd. Solid content concentration: 40% by mass, particle size: 118 nm MP-2040: Silica particles manufactured by Nissan Chemical Co., Ltd. Solid content: 40% by mass, particle size: 190 nm Snowtex (registered trademark) 30: Silica particles manufactured by Nissan Chemical Co., Ltd. Solid content concentration: 30% by mass, particle size: 4.6 nm

[0054] [Table 1]

[0055] The measurement results of the crystallization time are shown in Figure 1. In Figure 1, the time when the amount of heat absorption per unit time shows a maximum value (peak) is indicated by an arrow. It was confirmed that Comparative Example 1, in which the number average particle diameter of the inorganic filler measured by dynamic light scattering is 190 nm, Comparative Example 2, in which the number average particle diameter of the inorganic filler measured by dynamic light scattering is 4.6 nm, and Comparative Example 3, in which no inorganic filler is added, have a lower crystallization rate than Examples 1 to 3, in which the number average particle diameter of the inorganic filler measured by dynamic light scattering is 118 nm. A lower crystallization rate suggests a lower initial adhesive strength.

[0056] The adhesive compositions [C] of Example 1, Comparative Example 1, and Comparative Example 2 were immersed in polystyrene petri dishes to a depth of 1 mm, and dried at 23°C and a relative humidity of 50% for 24 hours to volatilize the solvent, thereby obtaining adhesives [D]. [D] The results of small-angle X-ray scattering analysis of the adhesive are shown in Figure 2.

[0057] In Example 1 and Comparative Example 2, the particle sizes obtained by small-angle X-ray scattering using formula (1) were 126 nm and 192 nm, respectively. Therefore, since the values ​​obtained were almost the same as the number average particle size measured by dynamic light scattering, scattering due to isolated particles was observed, and since even higher-order peaks could be confirmed, it was confirmed that silica was uniformly dispersed as primary particles in the dried adhesive layer [D]. On the other hand, in Comparative Example 2, the particle sizes obtained by small-angle X-ray scattering using formula (1) were 60 nm and 30 nm, and secondary aggregation is considered to have occurred in comparison with the number average particle size of 4.6 nm measured by dynamic light scattering of the inorganic filler. It is presumed that the crystallization promotion effect was not observed due to this secondary aggregation.

Claims

1. The method includes a step of mixing a chloroprene polymer latex with an inorganic filler having a number average particle diameter of 10 to 150 nm as measured by a dynamic light scattering method, The chloroprene polymer latex is polymerized at 3 to 20° C., The method for producing a pressure-sensitive adhesive composition, wherein the inorganic filler has a number average particle diameter of 100 to 130 nm as measured by a dynamic light scattering method.

2. The method for producing a pressure-sensitive adhesive composition according to claim 1 , wherein the inorganic filler is silica.

3. The method for producing a pressure-sensitive adhesive composition according to claim 2 , wherein the silica is colloidal silica particles.

4. The method for producing a pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein a volume ratio (based on solid content) of the chloroprene polymer latex to the inorganic filler is 2 to 40.

5. A method for producing a pressure-sensitive adhesive layer, comprising a step of drying the pressure-sensitive adhesive composition produced by the method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Waterrinnoil type contact adhesive

    JP1977030838A

  • Cooling method for objects

    JP1979005258A

  • Adhesive composition

    JP1983113224A

  • Packaging material for photographic sensitive material

    JP2002040598A

  • Aqueous adhesive dispersion

    JP2005528495A